A Cobalamin‐Dependent Radical SAM Enzyme Catalyzes the Unique Cα‐Methylation of Glutamine in Methyl‐Coenzyme M Reductase. Issue 32 (29th June 2022) - Gagsteiger, Jana; Jahn, Sören; Heidinger, Lorenz; Gericke, Lukas; Andexer, Jennifer N.; Friedrich, Thorsten; Loenarz, Christoph; Layer, Gunhild
Abstract: Methyl‐coenzyme M reductase, which is responsible for the production of the greenhouse gas methane during biological methane formation, carries several unique posttranslational amino acid modifications, including a 2‐( S )‐methylglutamine. The enzyme responsible for the Cα ‐methylation of this glutamine is not known. Herein, we identify and characterize a cobalamin‐dependent radical SAM enzyme as the glutamine C‐methyltransferase. The recombinant protein from Methanoculleus thermophilus binds cobalamin in a base‐off, His‐off conformation and contains a single [4Fe‐4S] cluster. The cobalamin cofactor cycles between the methyl‐cob(III)alamin, cob(II)alamin and cob(I)alamin states during catalysis and produces methylated substrate, 5′‐deoxyadenosine and S ‐adenosyl‐l ‐homocysteine in a 1 : 1 : 1 ratio. The newly identified glutamine C‐methyltransferase belongs to the class B radical SAM methyltransferases known to catalyze challenging methylation reactions of sp 3 ‐hybridized carbon atoms. Abstract : The enzyme responsible for the unique Cα ‐methylation of a glutamine residue within methyl‐coenzyme M reductase was identified. Biochemical, spectroscopic and mass spectrometric characterization clearly classify the newly identified glutamine C‐methyltransferase as a cobalamin‐dependent radical SAM enzyme and, thus, as a new member of the class B radical SAM methyltransferase family.